'A crazy clutter of the mediaeval, medical mind': Ken Russell, Peter Maxwell Davies and Modernist Medievalism in The Devils. Issue 1 (4th May 2022) - KOLASSA, ALEXANDER
Abstract: Ken Russell's 1971 film The Devils is a shocking historical drama which, eclipsed by its own battle against censorship, has only recently had a critical revival. A landmark musical collaboration central to that film remains unexplored: Peter Maxwell Davies wrote the score, which is heard in tandem with 'period' performances from David Munrow and the Early Music Consort of London. Though ostensibly historical, the film's disruptive atemporal style is elevated through an art of stylized anachronism. This collaboration mirrors Davies's opera  Taverner (premièred in 1972), not only because that too featured Munrow and his consort but also because Russell was supposed to direct its première. This article posits Davies's film score as a compelling work combining historicist compositional interests and a challenging aesthetic of excess within the popular context of mass cinematic spectacle. Informed by the close study of Davies's own manuscripts, it argues for new ways of understanding the role of a persistent past in the music of a resolutely modernist present.